1970
DOI: 10.1139/b70-281
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of leaf cells resulting from starvation after excision. I. Electron microscopic observations

Abstract: Mesophyll cells of Nicotiana glutinosa exposed to starvation in the light after leaf excision showed the following major changes: vacuolation of the cytoplast; rearrangement of chloroplast and nuclear material; accumulation of cytoplasmic crystals and of starch; evagination and increased perforation of the nuclear membrane; and lysis of the tonoplast. Rearrangement of chloroplast material resulted in extended, 3-dimensional arrays (pseudocrystalline bodies), composed of electron-dense globules 85–100 Å in diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Various studies suggest that chloroplasts 74 and nonchlorophyllcontaining plastids engulf portions of the cytoplasm. [75][76][77][78] According to the interpretion of Ragetli et al 74 their data showed chloroplasts sending out a protrusion that swirls around a portion of the cytoplasm, then encloses this cytoplasmic portion as it merges with the main plastid body again.…”
Section: Macroautophagymentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies suggest that chloroplasts 74 and nonchlorophyllcontaining plastids engulf portions of the cytoplasm. [75][76][77][78] According to the interpretion of Ragetli et al 74 their data showed chloroplasts sending out a protrusion that swirls around a portion of the cytoplasm, then encloses this cytoplasmic portion as it merges with the main plastid body again.…”
Section: Macroautophagymentioning
confidence: 99%
“…[75][76][77][78] According to the interpretion of Ragetli et al 74 their data showed chloroplasts sending out a protrusion that swirls around a portion of the cytoplasm, then encloses this cytoplasmic portion as it merges with the main plastid body again. An alternative interpretation suggested that the two outer membranes of the plastids invaginate (move inwards), thereby forming a space inside the plastid that is contiguous with the cytoplasm.…”
Section: Macroautophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations suggest, however, that the two situations are different. These include the apparent inability of the detached leaf to synthesize particular species of RNA (15) as well as differences in patterns of nuclease accumulation (33) and ultrastructural breakdown (25).…”
Section: Introductionmentioning
confidence: 99%
“…Several observations suggest, however, that the two situations are different. These include the apparent inability of the detached leaf to synthesize particular species of RNA (15) as well as differences in patterns of nuclease accumulation (33) and ultrastructural breakdown (25).In spite of the likely requirement for respiratory energy by the integrated process of leaf senescence, data are lacking on the respiratory metabolism of both attached and detached yellowing leaves. The present paper examines the esterification of '2P, into respiratory metabolites by discs from such leaves, using as a point of reference discs from nonsenescent green leaves.…”
mentioning
confidence: 99%